Breeding of root and tuber crops - Hahn, S.K.; Howland, A.K.; Wilson, J.E. (1977)
The constraint to the production of the root and tuber crops, cassava, yams and sweet potato in Nigeria and Africa were stated. Breeding methods most appropriate to these crops were discussed in terms of mating systems, creation of source populations, selection, and use of selections. Intervarietal hybridization, interspecific hybridization, and population improvement through cyclic selection and recombination procedures were discussed as methods of creating source populations. Factors affecting the effectiveness of selection and efficient methods of selection in order to make maximum genetic progress were discussed. Use of selections were briefly stated. Synthetics, composites, or single and double crosses of yam produced from true seed may be used at the farmer level. The research results and experiences of the Root and Tuber lmprovement Program of llTA were used for discussion tosupport the proposed new breeding schemes of root and tuber crops